First results of the renewed Uragan-2M torsatron - Beletskii, A.A.; Berezhnyj, V.L.; Burchenko, P.Ya.; Chechkin, V.V.; Chernyshenko, V.Ya.; Grigor’eva, L.I.; Gubarev, S.P.; Konovalov, V.G.; Kulaga, A.E.; Kurilo, D.V.; Lesnyakov, G.G.; Losin, A.V.; et al. (Вопросы атомной науки и техники, 2008)
The results of experimental investigation on the vacuum magnetic surfaces in the l=2 torsatron with an additional toroidal field Uragan-2M at wide varying operation parameters are presented. Also the first results on the wall conditioning in the Uragan-2M with the ECR and RF discharges in atmosphere of hydrogen in steady-state mode at low magnetic field, plasma production and heating with RF power are described. Представлено результати експериментального дослідження вакуумних магнітних поверхонь в l=2 торсатроні з додатковим магнітним полем Ураган-2М для широкої зміни операційних параметрів. Також описані перші результати підготовки першої стінки в Урагані-2М за допомогою ЕЦР і ВЧ розрядів в атмосфері водню в стаціонарному режимі при низькому магнітному полі, створення і нагріву плазми ВЧ потужністю. Представлены результаты экспериментального исследования вакуумных магнитных поверхностей в l=2 торсатроне с дополнительным магнитным полем Ураган-2М для широкого изменения операционных параметров. Также описаны первые результаты подготовки первой стенки в Урагане-2М при помощи ЭЦР и ВЧ разрядов в атмосфере водорода в стационарном режиме при низком магнитном поле, создания и нагрева плазмы ВЧ- мощностью.